PELINDUNGAN DATA PRIBADI TERHADAP PENGGUNA FINTECH LENDING DI INDONESIA - Muin, Indriani; Suhra, Amalia (Muhammadiyah Makassar University, 2024)
Considering the potential impacts and risks arising from the lack of comprehensive regulation of fintech growth in Indonesia by the government, it is important to pay attention to and regulate consumer protection effectively within the fintech ecosystem. Two significant risks if consumer protection is neglected are privacy and data security breaches, as well as data misuse. Hence, data security and personal information issues are increasingly becoming concerns since such data may contain information involving individuals' privacy rights.The aim of this study is to understand and analyze the development of Fintech Lending in Indonesia and the Protection of Personal Data for Fintech Lending Users. The method employed is normative research, analyzing legal sources as secondary data. The research findings indicate that the current development of Fintech Lending in Indonesia involves 101 companies, comprising 94 conventional providers and 7 Sharia-compliant providers. Fintech Lending users are advised to be more vigilant in keeping pace with technological advancements and developments. Keywords: Fintech lending, Data ProtectionFintech lending, Data Protection